The effect of malaria on childhood anemia in a quasi-experimental study of 7,384 twins from 23 Sub-Saharan African countries - Starck, Tim; Dambach, Peter; Rouamba, Toussaint; Tinto, Halidou; Osier, Faith; Oldenburg, Catherine E.; Adam, Maya; Bärnighausen, Till; Jänisch, Thomas; Bulstra, Caroline A. (Frontiers in Public Health, 2022)
BackgroundYoung children in Sub-Saharan Africa (SSA), particularly those from resource-limited settings, are heavily burdened by anemia and malaria. While malaria infected children frequently become anemic (hemoglobin < 110 g/L), anemia is a strongly multifactorial disease with many other risk factors than malaria. Due to the complex and often overlapping contributors to anemia, it remains challenging to isolate the true impact of malaria on population level hemoglobin concentrations.MethodsWe quantified the malaria-induced effect on hemoglobin levels in children under 5 years of age, leveraging data from 7,384 twins and other multiples, aged 6 to 59 months, from 57 nationally representative Demographic and Health Surveys (DHSs) from 23 SSA countries from 2006 to 2019. The quasi-experimental twin fixed-effect design let us minimize the impact of potential confounders that do not vary between twins.ResultsOur analyses of twins revealed a malaria-induced hemoglobin decrease in infected twins of 9 g/L (95% CI -10; -7, p<0.001). The relative risk of severe anemia was higher (RR = 3.01, 95% CI 1.79; 5.1, p<0.001) among malaria positive children, compared to malaria negative children. Conversely, malaria positive children are only half as likely to be non-anemic (RR = 0.51, 95% CI 0.43; 0.61, p<0.001).ConclusionEven after rigorous control for confounding through a twin fixed-effects study design, malaria substantially decreased hemoglobin levels among SSA twins, rendering them much more susceptible to severe anemia. This effect reflects the population-level effect of malaria on anemia.
Gesehen am 16.01.2023